Insight into the Optoelectronic Nature and Mechanical Stability of Binary Chalcogenides: A First‐Principles Study - Dr. Banat Gul; Md. Fayz‐Al‐Asad; Dr. Muhammad Salman Khan; Dr. Mostafizur Rahaman; Dr. Govindasami Periyasami; Dr. Hijaz Ahmad (ChemElectroChem, 2023)
Abstract The most promising candidates for solar cells and optoelectronic devices are the transition metals dichalcogenides. Here, we employed the well‐known density functional theory to examine the structural, optoelectronic, and elastic characteristics of novel binary chalcogenides. A direct band gap for ZrX2 and an indirect band gap for PtX2 materials were both confirmed by the band structure features. The valence and conduction band regions are formed by the interaction of the A‐d and X‐p bands. Both the formation energy and the cohesive energies are calculated. The phonon dispersion plots confirmed the stability of the structures. Furthermore, the significant optical constants are computed and explained for possible employment in the optoelectronic application. Our computed band gaps and refractive index were found to be inversely associated. The vital elastic properties are also calculated to discuss the mechanical stability of these materials. The greater bulk modulus and Young's modulus for ZrS2 as compared to the studied chalcogenides suggest this material to be harder and more compressible. The B/G values, confirm all the studied dichalcogenides to be ductile. The most ductile of these materials was ZrSe2 with a predicted B/G value of 7.65. The present work could primarily aid in the creation of diverse and potentially useful semiconducting devices and their applications.